Study on Biological Activity of Litsea monopetala From Panchthar District of Nepal - Khanal, Subash; Bhatt, Bishan Datt (Journal of Institute of Science and Technology, 2020)
The Panchthar, a hilly district of Eastern Nepal, has several medicinal plants which are used by indegenous people for the treatments of different diseases. In the present work, phytochemical and biological activities of hexane, ethyl acetate, acetone, and methanol extracts of Litsea monopetala leaves from the Pachthar district were analyzed. The phytochemical screening demonstrated the presence of major secondary metabolites like flavonoids, alkaloids, terpenoids, polyphenols, glycosides, and proteins. The antibacterial activity was estimated by the disc diffusion method against Bacillus substilus and Escherichia coli. The result showed that ethyl acetate extract exhibit the highest zone of inhibition (ZOI) value of 18 mm/disc. Acetone extract also showed significant antibacterial activity at the concentration of 100 mg/mL. Antioxidant activity from DPPH radical scavenging assay displayed the inhibitory concentration (IC50) values of dried methanol and acetone extracts were 30.74 μg/mL and 202.86 μg/mL, respectively. The methanol extract has the highest total phenolic content of 360.14 mg GAE/g extract and the highest total flavonoid content of 27.13 mg QE/g extract. The present study revealed that Litsea monopetala plant from the Panchthar district is a source of several bioactive substances and can be used in several drugs formulation.